Kadar Kadmium (Cd) dalam Urine pada Perokok Pasif - Nurhayana Nurhayana; Anung Sugihantono (Jaringan Laboratorium Medis, 2021)
Smoking is a familiar activity in daily life. The existence of filters on cigarettes, causes the danger of cigarette smoke to be felt more by passive smokers. One of the content of cigarette smoke is cadmium (Cd) which is one of the environmental pollutants that are harmful and accumulate in the tissues of living things. The purpose of this study is to measure and describe the levels of Cadmium (Cd) in the urine of passive smokers in RT 03 RW 06 Gandekan Hamlet, Harjosari, Bawen District, Semarang Regency. Using observational (non-experimental) research design with descriptive research criteria. The number of samples of 12 urine from the community of RT 03 RW 06 Gandekan Hamlet, Harjosari, Bawen Subdistrict, Semarang Regency. The results of the examination of Cadmium Levels (Cd) on the 13 samples of passive smoker urine in gandekan RT 01 RW 06 Harjosari Subdistrict, Bawen Subdistrict, Semarang District received the highest level of 0.074 mg/L and the lowest result -0.005 mg/L. Differences in cadmium levels in the passive smoker urine were caused by several factors such as age, environment, health status, occupation, and consumption of antioxidants and milk. Cadmium (Cd) levels in the urine of all passive smokers were in the normal category (2mg/L).